Mental Well-Being and Teaching Quality as Predictors of Educator Performance: Implications for Early Childhood Educators - Wiwik Suatin; Dimas Zuhri Ahmad (Universitas Islam Negeri Palopo, 2026)
The performance of educators is a decisive determinant of educational quality in Islamic educational institutions, yet it is shaped simultaneously by internal psychological conditions and external instructional practices that are rarely examined together. Although teacher welfare and professional development have attracted growing scholarly attention, empirical studies that test mental well-being and teaching quality jointly as predictors of educator performance in Islamic educational institutions, within which early childhood provision (RA/TK) is nested, remain scarce. This study examines the extent to which mental well-being and teaching quality, individually and jointly, predict the performance of educators at Baitun Naim Islamic Education Institute. Mental well-being was conceptualised through Ryff’s six dimensions of self-acceptance, personal growth, purpose in life, positive relations with others, environmental mastery, and autonomy, whereas teaching quality was operationalised through lesson planning, instructional implementation, assessment of learning outcomes, classroom management, and interpersonal relations with students. A cross-sectional quantitative survey design was employed. Sixty educators were drawn from a population of 82 through purposive sampling, and data were collected using a five-point Likert questionnaire whose reliability coefficients ranged from .904 to .951. The data were analysed using multiple linear regression in SPSS after classical assumption testing. Mental well-being (β = .398, t = 3.619, p = .001) and teaching quality (β = .487, t = 4.428, p < .001) were each positively and significantly associated with educator performance, and together the two predictors accounted for 68.2% of its variance, F(2, 57) = 61.03, p < .001. Teaching quality carried the larger standardised coefficient, although the confidence intervals of the two estimates overlap and the ordering is therefore reported as indicative rather than conclusive. Because the design is cross-sectional and all measures were self-reported, the findings are interpreted as associations rather than causal effects. The study integrates psychological and pedagogical predictors within a single multivariate framework and informs welfare and instructional-quality policy across the units of Islamic educational institutions, including early childhood provision.